The complementary facets of epithelial host defenses in the genetic model organism Drosophila melanogaster: from resistance to resilience. - Ferrandon, D. (Current Opinion in Immunology, 2013)
Significant advances have been made in our understanding of the host defense against microbial infections taking place at frontier epithelia of Drosophila flies. Immune deficiency (IMD), the major NF-?B immune response pathway induced in these epithelia, displays remarkable adaptations in its activation and regulation in the respiratory and digestive tract. The host defense against ingested pathogens is not limited to resistance, that is, the immune response. It also involves resilience, the capacity of the host to endure and repair damages inflicted by pathogens or the host's own immune response. For instance, enterocytes damaged by pathogens, the microbiota of aging flies, or host-derived reactive oxygen species (ROS), are replaced under the control of multiple pathways by the compensatory proliferation of intestinal stem cells (ISCs).